2002
DOI: 10.1074/jbc.m110352200
|View full text |Cite
|
Sign up to set email alerts
|

P2Y11 Receptors Activate Adenylyl Cyclase and Contribute to Nucleotide-promoted cAMP Formation in MDCK-D1Cells

Abstract: Cells commonly co-express multiple receptor subtypes that recognize the same physiological agonist, but it is difficult to define which among such receptor subtypes mediates a particular response. This can be a particularly vexing problem if subtype-selective agonists and antagonists are not available. One such example is P2Y receptors, which respond to ATP and other nucleotides, are expressed in a variety of tissues and cell types, and for which few subtype-selective antagonists exist (2-4). Our laboratory ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Indeed, exposure to these nucleotides increased the release of IL-10 (Figures 1 and 3), and IL-10 release mediated by ATP-γS (10 µM), BzATP (100 µM), and dATP (1 mM) was down-regulated by an adenylate cyclase inhibitor, SQ22536, and a PKA inhibitor, H-89 ( Figure 5B). These results are consistent with previous findings that P2Y 11 receptors activate adenylate cyclase and contribute to cAMP formation (Torres et al, 2002). Recent studies showed that ATP-γS enhanced LPS-induced IL-10 production in human monocyte-derived dendritic cells (Marteau et al, 2004), and that ATP-γS and BzATP inhibited the production of TNF-α, IL-8, and MIP-1β in human mast cells through a G s -coupled receptor (Feng et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, exposure to these nucleotides increased the release of IL-10 (Figures 1 and 3), and IL-10 release mediated by ATP-γS (10 µM), BzATP (100 µM), and dATP (1 mM) was down-regulated by an adenylate cyclase inhibitor, SQ22536, and a PKA inhibitor, H-89 ( Figure 5B). These results are consistent with previous findings that P2Y 11 receptors activate adenylate cyclase and contribute to cAMP formation (Torres et al, 2002). Recent studies showed that ATP-γS enhanced LPS-induced IL-10 production in human monocyte-derived dendritic cells (Marteau et al, 2004), and that ATP-γS and BzATP inhibited the production of TNF-α, IL-8, and MIP-1β in human mast cells through a G s -coupled receptor (Feng et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…The authors thought that ATP␥S might be functioning as a P2 agonist, but it failed to induce calcium flux in CD4 ϩ T cells. Furthermore, the CD4 ϩ T cells did not express P2Y 11 receptors, which could account for the increase in cAMP because they are the only P2 receptors that are coupled to both adenylyl cyclase and phospholipase C pathways (38,40). Our data suggest that E-NTPDase might be the target for ATP␥S-induced inhibition of cytokine secretion by activated CD4 ϩ T cells in the study reported by Duhant et al (34).…”
Section: Discussionsupporting
confidence: 60%
“…In hepatoma cells (Junankar et al, 2002), for example, released ATP is degraded to ADP to stimulate P2Y 1 receptors. In epithelial (Torres et al, 2002) and osteoblastic (You et al, 2002) cells, in contrast, released ATP itself activates P2Y 11 and P2Y 2 receptors, respectively. In PC12 cells, both types of autocrine-paracrine regulation occur under resting conditions and during depolarization and involve P2Y 12 and P2Y 2 receptors, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, neuronal ATP release is depolarization and Ca 2ϩ dependent (von Kugelgen et al, 1994). In non-neural tissues, such as liver, kidney, bones, and blood vessels, released nucleotides subserve autocrine-paracrine functions by activating certain P2Y receptors (Gerasimovskaya et al, 2002;Junankar et al, 2002;Schwiebert et al, 2002;Torres et al, 2002;You et al, 2002). In neurons, action potential-and Ca 2ϩ -dependent release of ATP contributes to synaptic transmission via P2X receptors (Robertson et al, 2001); however, much less is known about the activation of neuronal P2Y receptors by released nucleotides.…”
Section: Introductionmentioning
confidence: 99%